Immersive Attunement: Consciously Capturing Cultural Geo-Heritage Sites in Cinematic Virtual Reality - Tiisetso Dladla (Kronos)
This paper seeks to unpack the social, environmental and cultural impact that virtual reality (VR) photographic documentation has on sacred geo-heritage sites. Artistic and creative researchers have consciously or unconsciously practiced immersive at-tunement when visiting and creating digital art. Several of these sacred geo-heritage sites are protected for their geological, historical or cultural significance. Immersive attunement is the concept of immersing oneself in a foreign environment and being culturally conscious of the impact that the filmmaker's physical presence and the audience's virtual presence imposes on a given space. Cinematic virtual reality is a form of immersive media that creates a digitised cinematic experience using 360-degree cameras, designed to project a spherical image through a head-mounted display. This allows the audience to screen the VR film from inside the picture. Immersive media technology such as virtual reality cameras and photogrammetry drones are currently mapping geological sites around the world, for a myriad of scientific and artistic research. These projects offer the possibility of advancements in scientific understanding and artistic awakening. What social, cultural, and environmental impact do the researchers or artists photographing the site have on those specific environments? This paper aims to investigate ways in which immersive media artists can sustainably and consciously compose and photograph cultural geo-heritage sites for cinematic virtual reality experiences. What choices can immersive media artists make to consciously photograph these significant places using VR technology, without harming the environment? What are the ethical responsibilities of using these technologies in places that are not only culturally protected but sacred?